On analysis of the electromagnetic resistance of radioelectronic devices under impulse radiation - Lonin, Yu.Р.; Ponomaryov, A.G.; Chumakov, V.I. (Вопросы атомной науки и техники, 2018)
The results of investigations on degradation effects in the radioelectronics circuitry under the influence of the high-intensity pulse radiation are given. Analysis of the mechanism of degradation because of shortening the radio pulse radiation wavelength has been carried out. When the wavelength of the object, exposed to the radiation of a centimeter range, exceeds the characteristic size of structural elements, the degradation mechanism is conditioned by the quasi-static effects on the object structure inhomogeneities. The degradation effects manifest themselves in accordance with the concept of a "weak link" and localization damage model. In the case of wavelength shortening, when the characteristic size of the object structure element becomes commensurable with the wavelength, the resonance effect action is more and more increasing. The degradation redistribution occurs according to the field intensity distribution in the resonant regions. The problem of electromagnetic resistance lowering, under conditions of the tendency towards the radio electronics circuitry microminiaturization, is discussed.